2021
DOI: 10.1126/scitranslmed.abc6245
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced drug delivery to the reproductive tract using nanomedicine reveals therapeutic options for prevention of preterm birth

Abstract: Inflammation contributes to nearly 4 million global premature births annually. Here, we used a mouse model of intrauterine inflammation to test clinically used formulations, as well as engineered nanoformulations, for the prevention of preterm birth (PTB). We observed that neither systemic 17a-hydroxyprogesterone caproate (Makena) nor vaginal progesterone gel (Crinone) was sufficient to prevent inflammation-induced PTB, consistent with recent clinical trial failures. However, we found that vaginal delivery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 90 publications
0
32
0
Order By: Relevance
“…These mucoinert nanosuspensions have been shown to improve the vaginal administration of progesterone and prevent progesterone withdrawal (RU486)-induced preterm birth in mice, while avoiding stimulating myometrial expression of inflammatory cytokines [286]. Other studies have demonstrated successful vaginal administration of the histone deacetylase inhibitors trichostatin-A (TSA) and suberoylanilide hydroxamic acid (SAHA) via mucoinert nanosuspensions [287]. Nanosuspensions of TSA in combination with progesterone had anti-inflammatory effects on myometrial gene expression and were effective in significantly reducing rates of LPS-induced preterm birth in mice, whereas nanosuspensions of progesterone alone were not effective [287].…”
Section: Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…These mucoinert nanosuspensions have been shown to improve the vaginal administration of progesterone and prevent progesterone withdrawal (RU486)-induced preterm birth in mice, while avoiding stimulating myometrial expression of inflammatory cytokines [286]. Other studies have demonstrated successful vaginal administration of the histone deacetylase inhibitors trichostatin-A (TSA) and suberoylanilide hydroxamic acid (SAHA) via mucoinert nanosuspensions [287]. Nanosuspensions of TSA in combination with progesterone had anti-inflammatory effects on myometrial gene expression and were effective in significantly reducing rates of LPS-induced preterm birth in mice, whereas nanosuspensions of progesterone alone were not effective [287].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Other studies have demonstrated successful vaginal administration of the histone deacetylase inhibitors trichostatin-A (TSA) and suberoylanilide hydroxamic acid (SAHA) via mucoinert nanosuspensions [287]. Nanosuspensions of TSA in combination with progesterone had anti-inflammatory effects on myometrial gene expression and were effective in significantly reducing rates of LPS-induced preterm birth in mice, whereas nanosuspensions of progesterone alone were not effective [287]. Similarly, nanoformulations of the sphingosine kinase (SphK) inhibitor (SKI II) were developed, as SphK inhibition was previously shown to prevent LPS-induced preterm birth in mice [288].…”
Section: Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetration enhancers may also be used, though frequent and chronic dosing can lead to ocular irritation and toxicity 24 . An alternative approach that has been demonstrated for a wide variety of mucosal surfaces, including the eye, female reproductive tract, gastrointestinal tract, and airways is to formulate nanoparticles with mucoinert surface coatings 25,26 . These so‐called mucus‐penetrating particles (MPP) are nonadhesive to the sticky mucin proteins and small enough in size to fit through the net‐like pores, leading to enhanced delivery of small‐molecule drugs and nucleic acids alike 25 .…”
Section: Introductionmentioning
confidence: 99%
“… 24 An alternative approach that has been demonstrated for a wide variety of mucosal surfaces, including the eye, female reproductive tract, gastrointestinal tract, and airways is to formulate nanoparticles with mucoinert surface coatings. 25 , 26 These so‐called mucus‐penetrating particles (MPP) are nonadhesive to the sticky mucin proteins and small enough in size to fit through the net‐like pores, leading to enhanced delivery of small‐molecule drugs and nucleic acids alike. 25 In the context of eye drops, MPP provide rapid and enhanced intraocular drug absorption, leading to the Food and Drug Administration (FDA) approval of two loteprednol etabonate (LE)‐based products for treating ocular inflammation and pain.…”
Section: Introductionmentioning
confidence: 99%